Radical Reform: Studi Analitis Konsep Ijtihad Tariq Ramadan - Soesanto, Abimanyu Iqbal (AL-MANHAJ: Jurnal Hukum dan Pranata Sosial Islam, 2022)
This article wants to discuss the concept of Ijtihad in the perspective of Tariq Ramadan. Thus, at the same time, this article pays attention to the concept of Radical Reform which is an effort to achieve Tariq Ramadan, as an Islamic activist who is involved in the dynamics of Muslim life in Europe. This article is a qualitative article using a library research methodology. The primary data from this article is Tariq Ramadan's book, Radical Reform: Islamic Ethic and Liberation, while the secondary data from this research are books, journals and articles. supporting articles. This article finds that the ideas brought by Tariq Ramadan are relevant to be applied by minority Muslims in the west, because in this idea Ramadan does not only adapt or rely on contextualization, but emphasizes that the situation or context is an independent aspect. This article argues that the offer of Ijtihad in Ramadan's Radical Reform concept is the most suitable to be applied in the social reality where de facto a large number of Muslims live as a minority community, especially in the western world which has a population with various theological beliefs.